Value investing : tools and techniques for intelligent investment - Montier, James (West Sussex : Wiley, 2009)
The book explains how value investing is the only tried and tested method of delivering sustainable long-term returns.
Why everything you learned in business school is wrong -- The behavioural foundations of value investing -- The philosophy of value investing -- The empirical evidence -- The 'dark side' of value investing : short selling -- Real-time value investing.
Includes bibliographical references and index.
nif 26/04/13
Loans
Keywords: Value investing; Investment analysis; Corporations -- Valuation